Um olhar sobre a história: características e tendências da produção científica na área de História no Brasil (1985-2009) - Aguiar, Renata Regina Gouvêa Barbatho de (2011)
The development of science in Brazil is a result of financial investments and advances in today technology. The goal of this research was to analyze the literature produced by historians and its institutional profile, observing their preferred communication channels, their trends of themes, and their geographical concentrations of Brazilian historiography over the past 25 years, to observe then the impacts of changes in Historiography. For this, we used the academic information of CNPq Productivity 1 Scholarship Fellows that are available in their Lattes Curriculum and in information on the History Graduate Program, through the institutional sites of these courses and of Capes. The methodology used was Bibliometrics that allowed quantifying and assessing the communicative profile of the scientific community in question. It was possible to conclude that the area of history is really growing, and that growth is influencing their production. The largest concentration of graduate studies program is located in Southeast, specifically in the states of Rio de Janeiro and Sao Paulo, and it is repeated with regard to the number of CNPq Productivity 1 Scholarship Fellows. Regarding communicative channels, as well as Ferrez (1981) concluded, and Brasil (1992) agreed, this research supports the importance of book in this area of expertise, however, other channels are beginning to emerge in the literature reviewed, emerging as a new alternative production demands, such as book chapters and articles in scientific journals, which are present in great expansion. It was identified that three foreign languages are found in measured publications, they are Spanish, French and English, in which English is more frequent. Finally, this research concludes that, once more as it had been identified by Ferrez and Brasil, the historian publishes predominantly on individual authorship, existing exceptionally published works with two authors